Genome-wide characterization and comparative expression profiling of dual-specificity phosphatase genes in yellow catfish (Pelteobagrus fulvidraco) after infection with exogenous Aeromonas hydrophila - Guo, Shengtao; Zeng, Mengsha; Zhang, Chenhao; Fan, Yuxin; Ran, Miling; Song, Zhaobin (Frontiers in Immunology, 2024)
In many mammals, dual-specificity phosphatases (DUSPs) are not only the key regulators of dephosphorylation and inactivation of mitogen-activated protein kinases (MAPKs), but also play an indispensable role in immune responses. However, members of the DUSP family in teleost (such as the representative yellow catfish, Pelteobagrus fulvidraco) have never been systematically analyzed before. In this study, we identified eight pfDusp genes, pfDusp1-7 and pfDusp10, in yellow catfish for subsequent characterization of their molecular features and expression patterns. Our results demonstrate that the deduced protein sequences exhibit two conserved sites, Leu-Phe-Leu-Gly and Ala-Tyr-Leu-Met, in the DSPc domain of these DUSP proteins. Genome-wide searching localized the eight DUSP encoding genes on seven chromosomes without any gene duplication. More comparative analyses of functional domains, genomic synteny, and phylogenetic tree support the high conservation of these Dusp genes in various vertebrates. Interestingly, it seems that Dusp3 may be an intermediate form of diverse Dusp genes during the process of evolution. Significant upregulation of Dusp transcripts in the kidney of yellow catfish after infected by A. hydrophila implies that these genes are potentially involved in the immune response to exogenous bacteria in yellow catfish. In summary, our genomics and transcriptomics analyses improve our understanding of the molecular evolution as well as the physiological roles of the DUSP family in the immune response of yellow catfish to exogenous bacterial pathogens, which may benefit practical aquaculture and molecular breeding of high bacteria-resistant fish variety.